A current-based algorithm for one-end fault location in series capacitor compensated double-circuit transmission lines. (March 2023) - Taheri, Reyhaneh; Eslami, Mahdiyeh; Damchi, Yaser
Abstract: Fault location is essential in series capacitor compensated double-circuit transmission lines regarding their capacity in transferring large amounts of power. The main challenge in the fault location of these lines is the nonlinear behavior of the metal-oxide varistor (MOV) in protecting the series capacitor against overvoltage during faults. In this paper, considering the MOV model and zero-sequence mutual coupling impedance between the two circuits, a new algorithm is presented for the location of single-line-to-ground faults, using currents measured at one end of the line. In this algorithm, first, a fault location is obtained for each data window, and then the exact location is calculated using statistical techniques. The proposed algorithm is independent of the measured voltages, and as a result, no error in the voltage measurement affects its accuracy. In addition, needing no telecommunication channel to access the data of the remote substation leads to reliability increasing and cost reductions. Not requiring pre-fault data is another advantage of the algorithm. The results indicate that the algorithm is independent of fault location and resistance, fault occurrence time, load conditions, and compensation level. In addition, the fault location error in all scenarios is within the standard range.